ANALISIS SALURAN, MARGIN, DAN EFISIENSI PEMASARAN TELUR ITIK DI KECAMATAN AIR HANGAT KABUPATEN KERINCI - Andica Dwi Beja Kurniawan; Fatati; Nahri Idris (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aimed to analyze the marketing channels, margins, and marketing efficiency of duck eggs in Air Hangat District, Kerinci Regency. This research was motivated by the marketing condition in which long distribution chains cause farmers to receive a lower share of the selling price. The study used a survey method with a census approach involving the entire population of duck farmers and duck egg traders as respondents. The data consisted of both primary and secondary data. Primary data were obtained through direct interviews with farmers and traders regarding production quantity, buying and selling prices of duck eggs, and the income earned. Secondary data were collected from related institutions and previous studies. Data analysis was conducted using marketing margin, farmer’s share, and marketing efficiency calculations. The results showed that there were two marketing channel patterns: (1) farmer → consumer, and (2) farmer → collector → retailer → consumer. The total marketing margin was IDR 1,172.49 per egg, with farmer’s share values of 100% and 65.77% for each channel, respectively. The marketing efficiency values were 0% for channel I and 3.07% for channel II. These findings indicate that channel I is the most efficient and provides greater benefits to farmers. It is recommended that farmers utilize shorter marketing channels or sell directly to consumers to increase their income.